Trait emotional intelligence in mothers of children with autism spectrum disorders - Marisavljević, Maša (Primenjena psihologija, 2023)
Studies that point to the difficulties in terms of communication, social skills, reading and interpreting emotions in parents of children with autism spectrum disorder (ASD), as well as those regarding the protective function of trait emotional intelligence (TEI), are not complemented by studies directly comparing TEI of caregivers of children with ASD and those of neurotypical children. The aim of this study was to examine differences in TEI between mothers of children with ASD and mothers of children of typical development, as well as the effect of different sociodemographic factors on maternal TEI. Participants were 156 mothers, divided into two groups: 1) mothers of children with ASD (ASD group) (N = 78) and 2) mothers of neurotypical children (control group) (N = 78). Participants completed the Serbian adaptation of the Trait Emotional Intelligence Questionnaire (TEIQue), short form, and answered various questions about their own and their children’s sociodemographic characteristics. Results suggest equivalence of global and factor-level TEIQue scores. Inspection of facet-level differences revealed higher scores on Stress management, and lower scores on Assertiveness in the ASD group compared to controls. Maternal age was not related to their TEI, while Well-being and Optimism of mothers decreased with increasing of ASD child`s age. Mothers with lower education had significantly lower TEI scores on several factors and facets regardless of the child’s ASD status. Obtained findings significantly contribute to the knowledge of perceived emotional self-efficacy in mothers of children with ASD which could elicit additional research and various mental health professional programs aimed at this vulnerable population.